Effects of coffee pericarp and litter mulsching on soil microbiomes diversity and functions in a tropical coffee plantation, South China - Zhao, Shaoguan; Zhang, Ang; Zhao, Qingyun; Zhang, Yaoyu; Wang, Dong; Su, Lanxi; Lin, Xingjun; Sun, Yan; Yan, Lin; Wang, Xianwen; An, Na; Dong, Yunping; et al. (Frontiers in Microbiology, 2024)
In recent decades, ecological cyclic cultivation models have attracted increasing attention, primarily because the decomposition of crop residues and litter enhances soil organic matter content, thereby altering the soil microenvironment and regulating the diversity and functions of soil microbial communities. However, the effects of different coffee waste mulching on the diversity of soil microbial 2 communities and their functions are still unclear. Therefore, this study set up four kinds of covering treatments: uncovered coffee waste (C), covered coffee litter (L), covered coffee pericarp (P) and covered both coffee litter and pericarp (PL). The results showed that: compared to the control, coffee pericarp mulching significantly increased the soil available potassium (SAK) content by 18.45% and alkali hydrolyzed N (SAN) content by 17.29%; coffee pericarp mulching significantly increased bacterial richness and diversity by 7.75% and 2.79%, respectively, while litter mulching had little effect on bacterial abundance and diversity was smaller; The pericarp mulching significantly increased the abundance of Proteus by 22.35% and the abundance of Chlamydomonas by 80.04%, but significantly decreased the abundance of Cyanobacteria by 68.38%, while the coffee litter mulching significantly increased the abundance of Chlamydomonas by 48.28%, but significantly decreased the abundance of Cyanobacteria by 73.98%. The increase in soil SAK promoted bacterial Anoxygenic_photoautotrophy, Nitrogen_respiration, Nitrate_respiration, Nitrite_respiration and Denitrification functions. The above results indicates that the increase in soil available potassium and alkali hydrolyzed N content under coffee pericarp cover is the main reason for promoting the diversity and richness of bacterial community and promoting the changes of bacterial community structure and function. The use of coffee pericarps in coffee plantations for ecological recycling helps to improve the diversity of the soil microbial community and maintain the relative stability of the microbial community structure and function, promoting soil health conservation and the sustainable development of related industries.